LIQUEFACTION SUSCEPTIBILITY MAP OF GREECE - Papathanassiou, G.; Valkaniotis, S.; Chaztipetros, Al.; Pavlides, S. (Bulletin of the Geological Society of Greece, 2010)
The basic goal of this study is the delineation of liquefaction susceptibility zones by correlating geological, geomorphological, seismological and past liquefaction occurrences information. A liquefaction susceptibility map should be used as a screening guide by decision makers for avoiding in advance prone to liquefaction areas. In order to compile this map, we took into consideration published data regarding the surficial distribution of geological units (IGME), the seismic hazard zonation in Greece as it is defined by the Earthquake Palling and Protection Organization and the distribution of historical liquefaction occurrences provided by the relatively database DALO v1.0 http://users.auth.gr/gpapatha/dalo.htm ). Initially, Quaternary age deposits were classified into categories of susceptibility based on their age and depositional process, having considered the designed value of acceleration. Afterwards, areas where past liquefaction occurrences were reported have been upgraded one level. The result obtained by this study is that as very high susceptibility zones are considered the coastal areas at the Ionian Islands and at the Gulf of Corinth